Rekognisi dan Kewarganegaraan di Indonesia: Analisis terhadap Program Peduli Lakpesdam NU - Amin Mudzakkir (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2021)
In the contemporary era, recognition or recognition is very crucial. However, instead of understanding it only culturally, recognition includes broad dimensions, including attempts to place one's or group's status in social and economic structures. This understanding derived from Nancy Fraser is used to analyze the activities of the Lakpesdam PBNU